An in vitro study on the effects of serum proteins on Enterococcus faecalis adhesion to three types of root sealers and gutta-percha - Xinwei Lin; Danlu Chi; Qimei Gong; Zhongchun Tong (BMC, 2021)
Abstract Background The extrusion of overfilled materials that extend beyond the apical foramina into the periradicular tissue may serve as a reservoir for bacterial adhesion and further affect recovery from periapical diseases. The aim of this study was to evaluate the effects of serum proteins on Enterococcus faecalis adhesion and survival on the surface of a calcium hydroxide-based root canal sealer (Apexit Plus), an epoxy resin sealer (AH-Plus) and a bioceramic sealer (iRoot SP). Methods Apexit Plus, AH-Plus and iRoot SP were evenly coated on gutta-percha, using gutta-percha alone as the control. After root canal sealer setting, the number of E. faecalis adhering to the root canal sealers and gutta-percha was counted in fetal bovine serum (FBS) or tryptic soy broth supplemented with 1% glucose (TSBG) by viable cell plate counts. The morphology of 7-day-old E. faecalis biofilms in FSB and TSBG was observed by scanning electron microscopy (SEM). Furthermore, E. faecalis biofilms on the three root canal sealers were labeled with a LIVE/DEAD BacLight™ Bacterial Viability Kit, and the ratios of viable to dead cells were analyzed using laser scanning microscopy operative software (Zen software). Results In the assays, after 1 and 7 days, the number of E. faecalis adhering to the root canal sealers or gutta-percha in FBS were significantly lower than those in TSBG (P < 0.05). In FBS, E. faecalis adhesion to iRoot SP and gutta-percha was reduced to a greater extent than that adhered to Apexit Plus and AH-Plus. Few E. faecalis accumulated on iRoot SP in FBS, whereas many bacteria assembled on iRoot SP and formed biofilms in TSBG. The ratio of viable cells in the E. faecalis biofilm on iRoot SP was the lowest. Conclusions Calcium hydroxide-based root canal sealers, epoxy resin sealers and bioceramic sealers may provide a substrate for E. faecalis adhesion, and the bioceramic sealer in this study showed the least E. faecalis adhesion in the presence of serum proteins compared to the other two sealers.